Anthropogenic threats to evolutionary heritage of angiosperms in the Netherlands through an increase in high‐competition environments. Issue 6 (9th September 2020) - Bartish, Igor V.; Ozinga, Wim A.; Bartish, Mark I.; Wamelink, G.W. Wieger; Hennekens, Stephan M.; Yguel, Benjamin; Prinzing, Andreas
Abstract: Present biodiversity comprises the evolutionary heritage of Earth's epochs. Lineages from particular epochs are often found in particular habitats, but whether current habitat decline threatens the heritage from particular epochs is unknown. We hypothesized that within a given region, humans threaten specifically habitats that harbor lineages from a particular geological epoch. We expect so because humans threaten environments that dominated and lineages that diversified during these epochs. We devised a new approach to quantify, per habitat type, diversification of lineages from different epochs. For Netherlands, one of the floristically and ecologically best‐studied regions, we quantified the decline of habitat types and species in the past century. We defined habitat types based on vegetation classification and used existing ranking of decline of vegetation classes and species. Currently, most declining habitat types and the group of red‐listed species are characterized by increased diversification of lineages dating back to Paleogene, specifically to Paleocene‐Eocene and Oligocene. Among vulnerable habitat types with large representation of lineages from these epochs were sublittoral and eulittoral zones of temperate seas and 2 types of nutrient‐poor, open habitats. These losses of evolutionary heritage would go unnoticed with classical measures of evolutionary diversity. Loss of heritage from Paleocene‐Eocene became unrelated to decline once low competition, shade tolerance, and low proportion of non‐Apiaceae were accounted for, suggesting that these variables explain the loss of heritage from Paleocene‐Eocene. Losses of heritage from Oligocene were partly explained by decline of habitat types occupied by weak competitors and shade‐tolerant species. Our results suggest a so‐far unappreciated human threat to evolutionary heritage: habitat decline threatens descendants from particular epochs. If the trends persist into the future uncontrolled, there may be no habitats within the region for many descendants of evolutionary ancient epochs, such as Paleogene. Abstract : Article impact statement : A new method shows that a regional flora is losing heritage of oldest geological epochs by losing habitats of low competition intensity. Abstract : Amenazas Antropogénicas para la Herencia Evolutiva de las Angiospermas en los Países Bajos a partir del Incremento en los Ambientes de Competencia Elevada Resumen: La biodiversidad actual abarca la herencia evolutiva de las épocas de la Tierra. Los linajes de épocas particulares se encuentran con frecuencia en hábitats particulares pero desconocemos si la declinación contemporánea de los hábitats amenaza a la herencia de una época en particular. Nuestra hipótesis supone que dentro de una región determinada, los humanos son una amenaza específica para los hábitats que albergan linajes de una época geológica particular. Suponemos esto pues los humanos amenazan a los ambientes y a los linajes que se diversificaron durante estas épocas. Diseñamos una nueva estrategia para cuantificar, por tipo de hábitat, la diversificación de los linajes de épocas distintas. Cuantificamos para los Países Bajos, una de las regiones mejor estudiada florística y ecológicamente, la declinación de los tipos de hábitat y de especies durante el siglo pasado. Definimos los tipos de hábitat con base en la clasificación de la vegetación y usamos las jerarquías existentes de la declinación de clases y especies de vegetación. Hoy en día, la mayoría de los tipos de hábitat en declinación y el grupo de especies en lista roja se caracterizan por la diversificación incrementada de los linajes que datan del Paleógeno, específicamente el Paleoceno‐Eoceno y el Oligoceno. Entre los tipos de hábitat vulnerables con una gran representación de los linajes de estas épocas encontramos a la zona sublitoral e intermareal de los mares templados y dos tipos de hábitats abiertos con deficiencia de nutrientes. Estas pérdidas de linaje evolutivo pasarían desapercibidas con las medidas clásicas de la diversidad evolutiva. La pérdida de la herencia del Paleoceno‐Eoceno dejó de estar relacionada con la declinación una vez que contabilizamos la baja competencia, la tolerancia a la sombra y la baja proporción de especies no pertenecientes a la familia Apiaceae, lo que sugiere que estas variables explican la pérdida de herencia del Paleoceno‐Eoceno. La pérdida de herencia del Oligoceno estuvo explicada en parte por la declinación de los tipos de hábitat ocupados por competidores débiles y especies tolerantes a la sombra. Nuestros resultados sugieren una amenaza humana para la herencia evolutiva que todavía no ha sido apreciada: la declinación del hábitat amenaza a los descendientes de épocas particulares. Si en el futuro las tendencias siguen sin ser controladas, puede que no haya hábitats en la región para muchos de los descendientes evolutivos de épocas antiguas, como el Paleógeno. 摘要: 现有的生物多样性包含了地球纪元以来的进化遗产。来自特定地质时期的谱系通常在特定的生境中被发现, 但是目前的生境丧失是否会威胁来自特定时期的进化遗产仍不得而知。我们假设在特定区域内, 人为威胁影响着特定地质时期的特定生境。提出这一假设是因为在特定的地质时期, 人类往往威胁着其自身主导的环境和当时多样化的谱系。我们设计了一种新方法来量化不同时期不同生境类型的谱系多样性。荷兰是植物区系和生态研究最好的地区之一, 我们量化了其在过去百年间生境类型和物种的丧失情况。我们基于植被分类来确定生境类型, 并利用已有的植被类型及物种丧失的信息进行了排序。目前, 大多数丧失的生境类型和列入红色名录的物种都具有古第三纪以来谱系多样性增加的特征, 特别是在古新世‐始新世和渐新世。在这些时期, 有大量代表性谱系的脆弱生境类型包括温带海洋的次大陆架和真沿岸地带, 以及两种缺乏营养的开放生境。这些生境中的进化遗产丢失在传统的进化多样性分析中不会被注意到。而如果将低竞争力、耐阴性和低比例非伞形科植物等因素纳入考虑, 则古新世‐始新世的进化遗产减少与生境和物种丧失无关, 说明这些变量可以解释古新世‐始新世时期的进化遗产的减少。此外, 竞争力弱的植物和耐阴物种所占据的生境类型的丧失可以部分解释渐新世的进化遗产减少。我们的研究结果展示了人类对进化遗产的威胁:生境丧失威胁着特定时期的谱系后代, 而这个问题目前尚未得到重视。如果这种趋势不受控制地继续发展, 那么在这个区域内可能就不再有进化远古时代 (如古第三纪) 的许多谱系的生境。翻译: 胡怡思; 审校: 聂永刚